PENDIDIK YANG IDEAL DALAM ISLAM (Sebuah Pandangan Haji Abdul Malik Karim Amrullah Tentang Pendidik yang Ideal Dalam Perspektif Islam) - Mu'in Abdullah (MAMBA'UL 'ULUM, 2018)
Educators are people who are responsible for the ongoing process of growth and development of the potential of students, both cognitive potential and psychomotor potential, to become ideal educators, the most important is the existence of praiseworthy character or akhlakul karimah because this trait is the basic foundation that must be owned by a person educator. Good and commendable personality is very important to be owned by an educator, because educators are the main figure for students in schools which is the most important part in shaping the character of students. Besides that the cultivation of morals and noble character for students is very important especially in this era where free association has become a trend for the younger generation. The ideal educator in Islam as in the words of Haji Abdul Malik Karim Amarullah (HAMKA), is devoted to giving knowledge, respecting student opinion, preventing reprehensible behavior, being polite and polite, being honest and honest, being fair and wise, and do not give a burden beyond the ability of learners.